PENGEMBANGAN E-MODUL SISTEM PENDINGIN MESIN UNTUK SISWA XI TKR SMK MUHAMMADIYAH GAMPING - Fuad Anwar Sudibyo; Samsul Hadi; Ardi Widyatmoko (Program Studi Pendidikan Vokasional Teknik Mesin, Universitas Sarjanawiyata Tamansiswa, 2021)
This study aims to determine the feasibility of a good and quality engine cooling system E-module. This research development model has four steps, including the preliminary study step, the development step, the field test step and the deployment step. The e-Module teaching materials were evaluated from two material experts and two media experts then tested on 16 XI TKR students of SMK Muhammadiyah Gamping. The collection of respondents used is a questionnaire / questionnaire Likert scale model of four coverage options. the acquisition of material expert score of 3.36 is included in the